THE IMPACT OF COMPLIMENT FOR THE STUDENTS ON THEIR INTEREST IN LEARNING ENGLISH - Aprianty, Nurul; Jabu, Baso; Sakkir, Geminastiti (Universitas Negeri Makassar, 2026)
This study aims to find out the impact of teacher compliments on students' interest in learning English. This research used a qualitative descriptive method. The data collection in this study was carried out by observing the atmosphere in the classroom during the learning process and interviewing 6 students from SMAN 7 Wajo. The results of this study found that compliment has a very positive impact on students' motivation and interest in learning. Teachers who consistently give compliments can create a more enjoyable learning atmosphere and increase students' interest in continuing to learn. Compliment also serves as a way to maintain student motivation, both intrinsic and extrinsic, which ultimately has a positive effect on the quality of learning.